Effectiveness of Computer‐Based Training on Toothbrush Skills of Patients Treated With Crowns: A Randomized Controlled Trial. Issue 11 (1st November 2016) - Deinzer, Renate; Harnacke, Daniela; Mengel, Reiner; Telzer, Maria; Lotzmann, Ulrich; Wöstmann, Bernd
Abstract : Background: This study was conducted to assess plaque removal skills in patients with fixed dental prostheses (FDP), and effectiveness of computer‐based training (CBT) of different brushing techniques (Fones versus Bass technique in their common modifications). Methods: Ninety‐three patients with FDP were randomly allocated to one of three training groups: 1) C (control group); 2) F (Fones technique group); and 3) B (Bass technique group). All patients received CBT of the basics of toothbrushing. Group C received no further instructions while groups F and B received additional CBT of the modified Fones or the modified Bass technique, respectively. Plaque levels were assessed immediately after patients had been asked to perform oral hygiene to the best of their abilities. Results: Prior to training, persistent plaque deposits were found at 80% of marginal sites of natural teeth immediately after patients had performed oral hygiene. Considerably fewer plaque deposits were found on FDP (43%). No significant group differences were observed 6 and 12 weeks after training, either for natural teeth or for FDP (all P >0.05). Conclusions: Plaque removal skills are low in patients with FDP. Apparently, they do not profit from CBT of the techniques studied here. Studies observing their actual brushing behavior should be conducted to elucidate reasons for their deficits and to explore why CBT does not work in this group of patients.